2012
DOI: 10.1016/j.yrtph.2012.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment for consumer exposure to toluene diisocyanate (TDI) derived from polyurethane flexible foam

Abstract: Polyurethanes (PU) are polymers made from diisocyanates and polyols for a variety of consumer products. It has been suggested that PU foam may contain trace amounts of residual toluene diisocyanate (TDI) monomers and present a health risk. To address this concern, the exposure scenario and health risks posed by sleeping on a PU foam mattress were evaluated. Toxicity benchmarks for key non-cancer endpoints (i.e., irritation, sensitization, respiratory tract effects) were determined by dividing points of departu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 70 publications
0
19
0
Order By: Relevance
“…The emerging recentt rend is the elaboration of non-isocyanate polyurethanes (NIPUs) because isocyanates are harmful and suspected to be carcinogenic. [14] Repeated exposure can lead to skin irritation and incurable respiratory problems, such as long-term asthma. Moreover,t he synthesis of isocyanates requires the use of noxiouss ubstances,s uch as phosgene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The emerging recentt rend is the elaboration of non-isocyanate polyurethanes (NIPUs) because isocyanates are harmful and suspected to be carcinogenic. [14] Repeated exposure can lead to skin irritation and incurable respiratory problems, such as long-term asthma. Moreover,t he synthesis of isocyanates requires the use of noxiouss ubstances,s uch as phosgene.…”
Section: Introductionmentioning
confidence: 99%
“…[1] The current challengei st os ubstitutef ossil resourcesb yr enewable ones to synthesize new promising molecules or building blocks for the elaboration of sustainable materials, especially new biobased polymers. [2] Biobased polymers are defined as either partly (> 20 %) or fully based on biomass (e.g.,from vegetable derivatives, animals, and microorganisms).B iobased contentsa re mainly determined throught he 14 Cc ontentb ecause fossil carbon resources no longer contain this isotope. [3] Among polymers, which can be biobased, and in recentd ecades, much attention has been paid to polyurethanes (PUs), which are one of the most common polymers used in industry.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that unreacted TDI is present in PUF [5,6]. However, these results have been questioned since it was not concluded whether the detected TDI stemmed from residual TDI or from foam degradation during extraction or derivatization procedures [7]. Figure 2 shows the conversion of an isocyanate to a primary amine.…”
Section: Fig 1: General Urethane Condensation Reactionmentioning
confidence: 99%
“…Diisocyanates (dNCOs) are highly reactive chemicals used as cross-linking agents in the manufacture of polyurethane products such as paints, elastomers, and adhesives 13 . They are potent sensitizers and are a commonly reported cause of occupational chemical hypersensitivity reactions including asthma 4,5 .…”
Section: Introductionmentioning
confidence: 99%